Influence of Weight-Bearing Computed Tomography in the New Staging System of Progressive Collapsing Foot Deformity Classification. Issue 1 (January 2022) - Mansur, Nacime S.; Lee, Hee Young; Ehret, Amanda; Lalevee, Matthieu; Iehl, Caleb J.; Myerson, Mark S.; Bernasconi, Alessio; Buedts, Kristian; Lintz, Francois; Netto, Cesar de Cesar
Category: Hindfoot; Midfoot/Forefoot Introduction/Purpose: The same Consensus that proposed a new nomenclature for Flatfoot, Progressive Collapsing Foot Deformity (PCFD), also introduced a new classification system for the disease. The idea of staging was supplemented by the construction of a system combining deformity classes and its flexibilities, using clinical and radiographic signs. The capacity of the weight-bearing computed tomography (WBCT) in evaluating PCFD and all components of peritalar subluxation has been established. The objective of this study was to compare PCFD classifications performed utilizing clinical and conventional radiographs (CR) findings with classifications established using clinical and WBCT findings. We hypothesized that evaluations considering WBCT would significantly change PCFD classifications, portraying a different picture of the disease. Methods: This retrospective IRB-approved case-control diagnostic study evaluated 89 consecutive PCFD feet (84 patients) with different presentations of the disease. Three fellowship-trained foot and ankle surgeons performed chart reviews and CR evaluations, determining PCFD classifications for the studied subjects. After a two-week washout period, the sequence was randomized, and a new classification was executed using clinical data and WBCT assessment. One of the readers repeated the WBCT evaluation two weeks later for intrarater reliability purposes. Assessments included presence or absence of classes, such as hindfoot valgus (A), midfoot abduction/sinus tarsi impingement (B), medial column instability (C), subtalar joint subluxation/subfibular impingement (D) and valgus of the ankle joint (E) as well as flexibility (1) and rigidity (2) of existing deformities. Fleiss kappa was used for interrater and Cohen's kappa for intrarater agreements. Differences between studied groups were determined by distribution comparison. Results: Mean BMI and age were 54.4 (+-17.1) and 33.6 (+-7.6) respectively. Interrater reliability was found to be moderate (0.55) and intrarater to be excellent (0.98). Evaluation using CR produced 22.8% of 1ABC, 13% of 1AC, 8, 7% of 1ABCD and 7% of 2EABCD as most prevalent classifications. WBCT assessment found 31.5% of 1ABC, 11.2% of 1ABCD, 10.1% of 2ABCDE and 5.6% 1ABCDE. Class A was the most frequent component in CR (93.5%) and WBCT (94.5%). Class B had a higher prevalence in WBCT (94.38%) than in CR (71.7%) as well as Classes C (89.9% and 88.0%), D (44.9% and 29.3%) and E (31.5% and 23.9%). The percentage of combined flexible (1) and rigid (2) deformities was also higher in the WBCT evaluation (39.3% compared to 35.8%). Conclusion: As the new classification proposes the combination of different PCFD components to better support clinical decisions, proper identification of the classes is mandatory for a complete diagnosis. WBCT showed a different rate of deformity recognition, which increased the incidence of all classes, especially B (midfoot abduction/sinus tarsi impingement) and D (peritalar subluxation/subfibular impingement). An excellent intrarater agreement was found, which infers reliability of patient assessment combining clinical and WBCT evaluation. The obtained information could help providers to enhance comprehension of the disease and to supply patients with the most precise individual care.